A new approach to fully-reversible watermarking in medical imaging with breakthrough visibility parameters. (August 2016) - Roček, Aleš; Slavíček, Karel; Dostál, Otto; Javorník, Michal
Highlights: A new fully-reversible watermarking method in medical imaging is proposed. The method combines advantages of three traditional approaches. Major part of medical image stays unchanged but it is still protected. High PSNR and SSIM achieved. Abstract: Securing of medical images against intentional or accidental modification is a general issue in modern radiology. Watermarking, with its data-centric security, is very convenient for this purpose. We proposed a new method of fully reversible watermarking in medical imaging by combining the advantages of three traditional approaches—Reversible, Zero and RONI watermarking. The new method achieves exceptionally high values of Peak Signal to Noise Ratio and Structural Similarity index. The article evaluates the pros and cons of current methods of watermarking in medical imaging. Keeping the pros and eliminating the cons of the methods allows a new approach. Specific methods are selected and their application in practice described in detail. Application of the proposed method on a database of 6000 medical images from common hospital operations delivers very promising results which are discussed at the end of the article.